2022
DOI: 10.1007/s11606-022-07412-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Care Among Individuals with Prediabetes in Primary Care: a Retrospective Cohort Study

Abstract: BACKGROUND:The incidence of diabetes in the general US population (6.7 per 1000 adults in 2018) has not changed significantly since 2000, suggesting that individuals with prediabetes are not connecting to evidence-based interventions. OBJECTIVE: We sought to describe the clinical care of individuals with prediabetes, determine patient factors associated with this care, and evaluate risk for diabetes development. DESIGN: Retrospective cohort study using linked claims and electronic health record data. PARTICIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This is complicated by the practical application of lifestyle advice in those with prediabetes. A recent clinical care study found that among 3888 patients with a laboratory diagnosis of prediabetes, 63.4% had glycemic testing within 12 months of diagnosis, but only 1.0% were provided with a nutrition counseling referral, and only 5.4% were prescribed metformin [21].…”
Section: Discussionmentioning
confidence: 99%
“…This is complicated by the practical application of lifestyle advice in those with prediabetes. A recent clinical care study found that among 3888 patients with a laboratory diagnosis of prediabetes, 63.4% had glycemic testing within 12 months of diagnosis, but only 1.0% were provided with a nutrition counseling referral, and only 5.4% were prescribed metformin [21].…”
Section: Discussionmentioning
confidence: 99%
“…Adult data has indicated that prediabetes is under-coded in claims data. One study of 3,888 adults with laboratory evidence of prediabetes showed that only 10.4% had a coded diagnosis of prediabetes within the following 12 months ( 28 ). Given the known high attrition rate for pediatric patients with T2D, this study classified subjects with a single HbA1C ≥ 6.5% with a diagnosis of T2D ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 Despite efficacy of these interventions, treatment of pre-diabetes in primary care settings remains underutilized. 9,10 Less is known about the utilization of such interventions in persons of color or those in underserved communities. The goals of this practice-based research activity are to improve the (1) identification of patients with pre-diabetes and (2) utilization of guideline-recommended interventions in a federally qualified health center.…”
Section: Example 1: Meeting Current Guideline Recommendations For Pre...mentioning
confidence: 99%